2005
DOI: 10.1081/clt-45072
|View full text |Cite
|
Sign up to set email alerts
|

Juniper Tar Poisoning

Abstract: Juniper tar (cade oil) is distilled from the branches and wood of Juniperus oxycedrus. It contains etheric oils, triterpene and phenols, and is used for many purposes in folk medicine. A case is reported of a previously healthy man who ingested a spoonful of home-made extract of Juniperus oxycedrus. The poisoning caused fever, severe hypotension, renal failure, hepatotoxicity, and severe cutaneous burns on the face. After supportive and symptomatic treatment, the patient improved and was discharged in a good c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…Koruk et al 2 reported of a previously healthy man who ingested a spoonful of extract of Juniperus oxycedrus . The poisoning caused fever, severe hypotension, renal failure, hepatotoxicity and severe cutaneous burns on the face.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koruk et al 2 reported of a previously healthy man who ingested a spoonful of extract of Juniperus oxycedrus . The poisoning caused fever, severe hypotension, renal failure, hepatotoxicity and severe cutaneous burns on the face.…”
Section: Discussionmentioning
confidence: 99%
“…Koruk et al 2 reported the presence of renal failure (urea=114 mg/dl, serum creatinine=4.7 mg/dl) in a man who ingested a spoonful of extract of Juniperus oxycedrus in order to cure his nephrolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, if accidentally ingested adverse effects such as fever, hypotension, renal failure, and hepatotoxicity have been reported. 50 …”
Section: Wood Tarmentioning
confidence: 97%
“…Sucu [13] ve Erdemir [24] , çok eski çağlardan günümüze, uyuz ve deri hastalıklarına karşı kullanılan kükürtün, deride sülfür, alkalik disülfür ve pentationik asit şekline geçerek antiparaziter ve fungisit etki gösterdiğini; Baytop [11] , Koruk ve ark. [25] ve Kaya [14] , ardıç katranının antiseptik ve antiparaziter etkilerinin, bileşimindeki fenol türevlerinden (gaiakol, etil, kreosol) ileri geldiğini ve ekstratlarının tıp ve veteriner hekimliğinde deri hastalık-larının (uyuz vb.) tedavisinde haricen kullanıldığını bildirmektedirler.…”
Section: Tartişma Ve Sonuçunclassified